Pengaruh Kinerja Lingkungan, Ekonomi dan Sosial Terhadap Kinerja Keuangan (Return On Equity) Perbankan di Asia Tenggara - Nahwan, Nahwan (Universitas Bengkulu, 2025)
Abstract: This study aims to examine the impact of the three pillars of sustainability—environmental, economic, and social—on the financial performance of banks in Southeast Asia, as measured by Return on Equity (ROE). As sustainability increasingly becomes an integral component of corporate strategy, this research investigates the extent to which the integration of sustainability dimensions into banking operations influences financial outcomes, particularly profitability. Using a quantitative research approach with panel data regression analysis, the study employs secondary data obtained from the annual and sustainability reports of selected banks across Southeast Asia. The environmental, economic, and social dimensions are assessed based on indicators derived from widely recognized sustainability reporting frameworks. The empirical findings indicate that among the three dimensions, only the social pillar exerts a statistically significant negative influence on ROE, while the environmental and economic dimensions do not exhibit a significant effect. This suggests that social investments, while important, may impose short-term financial burdens on banks, possibly due to high costs or a misalignment with core business strategies. Despite the lack of immediate financial benefits, the study underscores the importance of a balanced and strategic implementation of all three sustainability dimensions to ensure long-term financial resilience. These findings offer valuable insights for banking institutions, regulators, and stakeholders in emerging markets, and highlight the need to develop sustainability strategies that are both socially responsible and financially sustainable. Keywords: Environmental Performance, Economic Performance, Social Performance, Return On Equity (ROE), Sustainable Banking